Strategies for labelling of exogenous and endogenous extracellular vesicles and their application for in vitro and in vivo functional studies - Boudna, Marie; Campos, Andres Delgado; Vychytilova-Faltejskova, Petra; Machackova, Tana; Slaby, Ondrej; Souckova, Kamila (Cell communication and signaling, 2024)
This review presents a comprehensive overview of labelling strategies for endogenous and exogenous extracellular vesicles, that can be utilised both in vitro and in vivo. It covers a broad spectrum of approaches, including fluorescent and bioluminescent labelling, and provides an analysis of their applications, strengths, and limitations. Furthermore, this article presents techniques that use radioactive tracers and contrast agents with the ability to track EVs both spatially and temporally. Emphasis is also placed on endogenous labelling mechanisms, represented by Cre-lox and CRISPR-Cas systems, which are powerful and flexible tools for real-time EV monitoring or tracking their fate in target cells. By summarizing the latest developments across these diverse labelling techniques, this review provides researchers with a reference to select the most appropriate labelling method for their EV based research.
Keywords: Radiolabelling; Cre-loxP; Extracellular Vesicles; Exosomes; In vivo imaging; Bioluminescent labelling; extracelulární vezikuly; EV tracking; Magnetic resonance; Extracellular vesicles; CRISPR-Cas; Fluorescent labelling